Special Educational Needs: Understanding Drivers of Complaints and Disagreements in the English System - Cullen, Mairi Ann; Lindsay, Geoff (Frontiers in Education, 2019)
This paper explores why some special educational needs (SEN) disagreements become very distressing for parents and how such disagreements can be prevented or resolved. It is a qualitative study of the experiences of 78 parents (70 mother, 8 fathers) who participated in a national study of experiences of England’s SEN disagreement resolution system, 2015-17. The study took place in the context of the biggest reform of the English SEN legal landscape since the seminal Warnock Report in 1978: the Children and Families Act 2014. This legislation extended aspects of individual statutory rights for parents and for the child/young person with SEN and increased expectations of their meaningful involvement in the assessment of needs and planning of provision to meet those needs. It also had a much greater focus on partnership working as a way to prevent disagreements and made statutory the requirement to offer mediation to support early resolution of disagreements. Data were analysed using the Framework approach and interpreted in the light of stress theory and the ‘drama triangle’. The main findings are that disagreements are initially driven by a belief that the child’s SEN are not being met; and that complaints and disagreements are subsequently driven by experiences of delays and role dissonance during the process of seeking to have the child’s needs met. The parental experience of distress can be understood in the light of classic stress theory. The emotional intensity and metaphors of battle can be understood as part of a ‘drama script’. Prevention and early resolution are aided by professionals and practitioners showing empathy, having the knowledge, skills and understanding to do their job properly, taking responsibility to redress wrongs, by greater investment in the SEN system (staff, staff training, range of appropriate educational provision), and by parents offering peer support. This paper is unique in two ways: in covering parents’ experiences across the English SEN disagreement resolution system and in interpreting our findings using psychological frameworks to understand what drives the intensity of such disagreements – and therefore of the way through them to resolution and improved prevention.